Probing behavior of aposymbiotic green peach aphid (Myzus persicae) on susceptible Solanum tuberosum and resistant Solanum stoloniferum plants - Machado Assefh, Cristina Renata (2016)
The green peach aphid, Myzus persicae Sulzer (Hemiptera: Aphididae) is one of the potato important pests; it is the most efficient vector of potato viruses. Myzus persicae harbors the endosymbiotic bacteria Buchnera aphidicola which supplements their diet. There is increasing evidence that B. aphidicola is involved in plant–aphid interactions and we previously demonstrated that B. aphidicola disruption (aposymbiosis) affected the probing behavior of M. persicae on radish plants, delaying host plant acceptance. In this work, we evaluated the effect of aposymbiosis on the probing behavior of M. persicae on 2 Solanum species with different compatibility with M. persicae, Solanum tuberosum (susceptible) and Solanum stoloniferum (resistant) with the electrical penetration graph technique (EPG). To disrupt B. aphidicola, rifampicin was administered to aphids through artificial diets. Aposymbiotic aphids, on both plant species, showed increased pathway activities, mechanical problems with the stylets, and delayed salivation in the phloem. The extended time in derailed stylet mechanics affected the occurrence of most other probing activities; it delayed the time to the first phloem phase and prevented ingestion from the phloem. The effect of aposymbiosis was more evident in the compatible interaction of M. persicae–S. tuberosum, than in the incompatible interaction with S. stoloniferum, which generated the M. persicae–S. tuberosum interaction to become incompatible. These results confirm that B. aphidicola is involved in the plant–aphid interaction in relation to plant acceptance, presumably through a role in stylets penetration in the plant.